DVB‐S2X physical layer performance results over realistic channel models. (22nd July 2015) - Cioni, Stefano; Ginesi, Alberto
Summary: The second‐generation satellite digital video broadcasting (DVB‐S2) standard has been recently reviewed with the aim of improving its spectral efficiency over a wide range of signal‐to‐noise ratios (SNRs). In this paper, three typical satellite channel configurations have been presented, which are associated with the three main DVB‐S2 core markets: direct‐to‐home (DTH) broadcasting, broadband services, and distribution/contribution/high‐speed IP links. This work is focused on the physical layer performance analysis of the new DVB‐S2 extensions (DVB‐S2X) waveform under realistic satellite channel models. Particular emphasis has been devoted to the maximization of the spectral efficiency as a function of the transmission symbol rate and in combination with the roll‐off factor of the pulse‐shaping filter, in the presence of state‐of‐the‐art modulation and demodulation techniques. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, three typical satellite channel configurations have been presented, which are associated with the three main DVB‐S2 core markets: direct‐to‐home (DTH) broadcasting, broadband services, and distribution/contribution/high‐speed IP links. This work is focused on the physical layer performance analysis of the new DVB‐S2 extensions (DVB‐S2X) waveform under realistic satellite channel models. Particular emphasis has been devoted to the maximization of the spectral efficiency as a function of the transmission symbol rate and in combination with the rolloff factor of the pulse‐shaping filter, in the presence of state‐of‐the‐art modulation and demodulation techniques.